Insulin, insulin-like growth factor 1 and insulin-like growth factor binding protein 3 serum concentrations in patients with adenomatous colon polyps - Janiak, Adam; Oset, Piotr; Talar-Wojnarowska, Renata; Kumor, Anna; Małecka-Panas, Ewa (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
Introduction: Insulin stimulates colonic mucosal cells proliferation directly and by influencing the concentration of insulin-like growth factor 1 (IGF-1) and insulin-like growth factor binding protein 3 (IGFBP-3). Aim : To estimate serum concentrations of insulin, IGF-1, and IGFBP-3 and to determine the relationships between them and colorectal adenoma location, dysplasia grading, histological type, and size. Material and methods: The study included 60 patients with colorectal adenomatous polyps found on colonoscopy and confirmed pathologically. The control group consisted of 30 individuals with no positive findings on colonoscopy. All patients had their blood drawn for assessment of insulin, IGF-1, and IGFBP-3 serum concentrations. Results : One hundred and nine adenomas (6–40 mm in size) were found in 60 study patients. The average age of patients with multiple polyps was significantly higher than that of patients with single pathologies (61.1 vs. 56.7 years respectively (p < 0.05)). A higher adenoma incidence rate was observed in the distal portion of the colon than the proximal one (50 vs. 10 polyps respectively (p < 0.01)). Higher serum levels of IGF-1 and IGFBP-3 were found in patients with adenomatous polyps than in the control group. The average IGF-1 concentration in patients with adenomas located proximally was also significantly higher compared to those located distally (p < 0.05). The insulin concentration was similar in both groups and not related to clinical data of patients. Conclusions : The results indicate the role of IGF-1 and IGFBP-3 in early carcinogenesis of the large intestine, and IGF-1 particularly in malignant transformation in the proximal part of the organ.